Modelling Local Bubble analogs: synthetic dust polarization maps - Maconi, Efrem; Soler, J D; Reißl, Stefan; Girichidis, Philipp; Klessen, Ralf S.; Hennebelle, P; Molinari, S; Testi, L; Smith, R J; Sormani, Mattia C.; Teh, Jia Wei; Traficante, A (Monthly notices of the Royal Astronomical Society, 2023)
We present a study of synthetic observations of polarized dust emission at 353 GHz as seen by an observer within a cavity in the interstellar medium (ISM). The cavity is selected from a magnetohydrodynamic simulation of the local ISM with time-dependent chemistry, star formation, and stellar feedback in form of supernova explosions with physical properties comparable to the Local Bubble ones. We find that the local density enhancement together with the coherent magnetic field in the cavity walls makes the selected candidate a translucent polarization filter to the emission coming from beyond its domains. This underlines the importance of studying the Local Bubble in further detail. The magnetic field lines inferred from synthetic dust polarization data are qualitatively in agreement with the all-sky maps of polarized emission at 353 GHz from the Planck satellite in the latitudes interval 15° ≲ |b| ≲ 65°. As our numerical simulation allows us to track the galactic mid-plane only out to distances of 250 pc, we exclude the region |b| ≲ 15° from our analysis. At large galactic latitudes, our model exhibits a high degree of small-scale structures. On the contrary, the observed polarization pattern around the Galactic Poles is relatively coherent and regular, and we argue that the global toroidal magnetic field of the Milky Way is important for explaining the data at |b| ≳ 65°. We show that from our synthetic polarization maps, it is difficult to distinguish between an open and a closed galactic cap using the inferred magnetic field morphology alone.
Veröffentlicht: 22. Juni 2023
Gesehen am 09.10.2023